1997
DOI: 10.1212/wnl.48.6.1583
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors and Parkinson's disease

Abstract: To explore environmental risk factors for Parkinson's disease (PD) in Taiwan, we investigated 120 patients with PD and 240 hospital control subjects matched with patients on age (+/-2 years) and sex. Based on a structured open-ended questionnaire, we carried out standardized interviews to obtain history of exposure to environmental factors, including place of residence, source of drinking water, and environmental and occupational exposures to various agricultural chemicals. In the univariate analysis, the hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
405
2
7

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 566 publications
(424 citation statements)
references
References 1 publication
10
405
2
7
Order By: Relevance
“…In most studies of pesticides in relation to PD exposure was assessed retrospectively as a broad category, rather than examining specific substances. Of 38 case-control studies, 19 reported increased risk of PD [147,154,156,[289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] with ORs ranging between 1.3 and 3.7 for most studies. One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301].…”
Section: Case-control Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In most studies of pesticides in relation to PD exposure was assessed retrospectively as a broad category, rather than examining specific substances. Of 38 case-control studies, 19 reported increased risk of PD [147,154,156,[289][290][291][292][293][294][295][296][297][298][299][300][301][302][303][304] with ORs ranging between 1.3 and 3.7 for most studies. One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301].…”
Section: Case-control Studiesmentioning
confidence: 99%
“…A hospital-based study found an increased risk of PD with overall pesticide or herbicide use (OR 2.89, 95% CI 2.28-3.66); the risk increased with longer duration of exposure (OR 6.72, 95% CI 2.62-12.21 for more than 20 years of exposure versus none) [293]. One population-based study reported increased risk of PD following occupational exposure to pesticides (OR 2.25, 95% CI 1.27-3.99) without a dose-response relationship [290].…”
Section: Case-control Studiesmentioning
confidence: 99%
See 3 more Smart Citations